2019
DOI: 10.2139/ssrn.3410674
|View full text |Cite
|
Sign up to set email alerts
|

Bullshit Makes the Art Grow Profounder

Abstract: Across four studies participants (N = 818) rated the profoundness of abstract art images accompanied with varying categories of titles, including: pseudo-profound bullshit titles (e.g., The Deaf Echo), mundane titles (e.g., Canvas 8), and no titles. Randomly generated pseudo-profound bullshit titles increased the perceived profoundness of computer-generated abstract art, compared to when no titles were present (Study 1). Mundane titles did not enhance the perception of profoundness, indicating that pseudo-prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…For example, one study found that listeners reported greater enjoyment of music when they were told it was written by Mozart than when they were told it was written by a less prominent composer ( Fischinger et al, 2018 ). Similarly, with other artforms, individuals judge artworks to be less valuable if they are duplicates of the original ( Newman and Bloom, 2012 ), and find artworks to be more profound if they are coupled with a profound-sounding title ( Turpin et al, 2019 ). Together, this work suggests that contextual information outside the music itself can have a strong influence on a listener’s aesthetic experience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that listeners reported greater enjoyment of music when they were told it was written by Mozart than when they were told it was written by a less prominent composer ( Fischinger et al, 2018 ). Similarly, with other artforms, individuals judge artworks to be less valuable if they are duplicates of the original ( Newman and Bloom, 2012 ), and find artworks to be more profound if they are coupled with a profound-sounding title ( Turpin et al, 2019 ). Together, this work suggests that contextual information outside the music itself can have a strong influence on a listener’s aesthetic experience.…”
Section: Discussionmentioning
confidence: 99%
“…The link between bullshitting, favourable judgement and resourcing can be seen in a recent study of the evaluation of contemporary art. This study found that when abstract images were paired with randomly generated ‘bullshit’ titles, they were judged as being more profound than images which either had no title or a descriptive title (Turpin et al, 2019). In this context, bullshit was a low-cost strategy that encouraged evaluators to see an image as more valuable than they otherwise would.…”
Section: A Theory Of Bullshittingmentioning
confidence: 89%
“…More specifically, we propose that the ability to produce satisfying bullshit may have emerged as an energetically efficient strategy for achieving an agent's goals (such as acquiring status or impressing mates). That is, an agent can engage in the arduous process of acquiring expert skills in domains that they could then leverage to accomplish certain goals, or can utilize bullshit as a strategy that potentially produces the same benefits at a much smaller cost (Turpin et al, 2019). Of course, these strategies need not be mutually exclusive, as the ability to produce satisfying bullshit may help even highly skilled individuals achieve their goals over equally skilled peers.…”
Section: Discussionmentioning
confidence: 99%
“…Bullshitting, with its emphasis on impressing others without regard for truth or meaning (Frankfurt, 2009;Pennycook et al, 2015), may represent an energetically inexpensive strategy for social navigation. Indeed, past work provides initial evidence for this claim, demonstrating that indiscriminately attaching meaningless pseudo-profound bullshit titles to artworks increases their perceived profundity (Turpin et al, 2019). On this basis, it has been hypothesized that bullshit can be used to gain a competitive advantage in any domain of human competition where the criteria for determining who succeeds and fails at least partially relies on impressing others.…”
mentioning
confidence: 99%
See 1 more Smart Citation